Case Report: Gut and spleen anomalies associated with DYRK1A syndrome - Infantino, I.; Tocchioni, F.; Ghionzoli, M.; Coletta, R.; Morini, F.; Morabito, A. (Frontiers in Pediatrics, 2023)
DYRK1A syndrome has been extensively studied mainly concerning neurologic and other phenotypic features such as skeleton and craniofacial alterations. In the present paper we want to highlight unusual anomalies associated with a DYRK1A mutation: a 17 year old female patient with language and cognitive delay, microcephaly and an autistic disorder which was operated on for spleen torsion with anomalous gut fixation.